2019
DOI: 10.17843/rpmesp.2019.364.4724
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados al uso de servicios de salud oral en adultos mayores peruanos: análisis secundario de encuesta poblacional, 2018

Abstract: Objetivos. Identificar la prevalencia y factores asociados al uso de servicios de salud oral en adultos mayores (AM) peruanos durante el 2018. Materiales y métodos. Análisis secundario de los datos de 4874 AM peruanos de la Encuesta Demográfica y de Salud Familiar (ENDES) 2018. Se consideró el uso de servicio de salud oral (sí/no) en razón de los seis meses previos a la aplicación de la encuesta como variable dependiente, las variables independientes fueron: sexo, edad, área de residencia, nivel educativo, est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
4
12
0
5
Order By: Relevance
“…In this sense, it is noteworthy that in all the categories of the variables evaluated, the percentage of negative response for the use of oral health services was higher, which indicates a marked trend in the Peruvian population, also repeated in other regions (Gao et al, 2020;Nazir, 2018;Onyejaka et al, 2016 services depending on the place of residence (Alsuraim & Han, 2020;Aravena-Rivas & Carbajal-Rodríguez, 2021;Botello-Harbaum et al, 2012;Fisher-Owens et al, 2016;Hernández-Vásquez et al, 2019), as in the meta-analysis developed by Alsuraim & Han, which found an increase in the access of children under 12 years of age to dental services in countries with a lower level of development compared to more developed countries, due to the effect of globalization (Alsuraim & Han, 2020). This variability is consistent with the results related to the geographic domain of the Jungle, which recorded a lower probability of using oral health services than the inhabitants of (Azañedo et al, 2019).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this sense, it is noteworthy that in all the categories of the variables evaluated, the percentage of negative response for the use of oral health services was higher, which indicates a marked trend in the Peruvian population, also repeated in other regions (Gao et al, 2020;Nazir, 2018;Onyejaka et al, 2016 services depending on the place of residence (Alsuraim & Han, 2020;Aravena-Rivas & Carbajal-Rodríguez, 2021;Botello-Harbaum et al, 2012;Fisher-Owens et al, 2016;Hernández-Vásquez et al, 2019), as in the meta-analysis developed by Alsuraim & Han, which found an increase in the access of children under 12 years of age to dental services in countries with a lower level of development compared to more developed countries, due to the effect of globalization (Alsuraim & Han, 2020). This variability is consistent with the results related to the geographic domain of the Jungle, which recorded a lower probability of using oral health services than the inhabitants of (Azañedo et al, 2019).…”
Section: Introductionsupporting
confidence: 86%
“…The association between the use of oral health services and improved oral health status has been established when comparing similar socio-demographic backgrounds (Alsuraim & Han, 2020;Botello-Harbaum et al, 2012;Fisher-Owens et al, 2016). Likewise, various studies indicate that the Social Determinants of Health (SDOH) are associated in different ways with the use of oral health services, according to the particular characteristics of each population (Aravena-Rivas & Carbajal-Rodríguez, 2021;Azañedo et al, 2019;Dho, 2018;Hernández-Vásquez et al, 2019;Kino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies evaluated dental visits taking into account the last 12 months, contrary to our approach involving a 6-month interval. Other studies in older Peruvian adults have also reported low prevalences, when evaluating OHSU over a 12-month (21.7%) or a 6-month period (24.9%) in 2014 and 2018, respectively [15,30]. Despite the physiopathological link between oral health and diabetes [31], which involves a greater need for OHSU, in our study this association was controlled for socio-economic confounders.…”
Section: Discussionmentioning
confidence: 65%
“…La mayoría de los participantes pertenecen al área rural, lo que dificulta la accesibilidad a los servicios de salud más cercanos y al control médico. Estos resultados son similares a un estudio realizado en Perú, en el que pertenecer al área rural dificulta el acceso a los servicios de salud 21 . Dorothea Orem, en su teoría del autocuidado, menciona que autocuidarse es una función humana y reguladora; debe realizarse de forma continua e ir enfocada al autocuido para la prevención de enfermedades.…”
Section: Prácticas Inadecuadasunclassified